2019
DOI: 10.1177/1090198119831759
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Marketing at SNAP- and WIC-Authorized Retail Food Stores in the United States

Abstract: Background. Lower-income families in the United States are at increased risk for food insecurity and have higher rates of tobacco use. Many retailers accepting government food assistance benefits also sell tobacco products, whose marketing promotes smoking initiation and undermines quit attempts. We examined the presence of tobacco marketing in authorized retailers in the Supplemental Nutrition Assistance Program (SNAP) and/or Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Store type was highly associated with storefront ST advertising, similarly to the study by Widome and associates (25), with convenience stores being more than 16 times more likely to have exterior ST advertisements than mass merchandisers, drug, or grocery stores. Similarly to Roberts and associates' findings (24), our study found a small but significant association between ST advertising in urban or metropolitan vs. more rural areas, and reported evidence of differential tobacco marketing at the point-of-sale, which disproportionately targeted urban and African American communities (22). This is especially troublesome, given the large percentage of convenience stores available to youth in metropolitan areas.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Store type was highly associated with storefront ST advertising, similarly to the study by Widome and associates (25), with convenience stores being more than 16 times more likely to have exterior ST advertisements than mass merchandisers, drug, or grocery stores. Similarly to Roberts and associates' findings (24), our study found a small but significant association between ST advertising in urban or metropolitan vs. more rural areas, and reported evidence of differential tobacco marketing at the point-of-sale, which disproportionately targeted urban and African American communities (22). This is especially troublesome, given the large percentage of convenience stores available to youth in metropolitan areas.…”
Section: Discussionsupporting
confidence: 79%
“…Approximately one third of retailers (34%) were located in census tracts in which the population was in the top quartile for having a high school education or less, and more than one fifth (23%) were located in the top quartile for having children under the age of 18 years. Additionally, two thirds of retailers (67%) were located in census tracts in the highest quartile for living in poverty as defined by the US Census Bureau (22). More than one tenth were located in census tracts in the highest quartile for percentage of Black race (15%), more than one third were in census tracts in the highest quartile for the percentage of American Indian race (35%), and one fifth (22%) were in census tracts with the highest percentage of Hispanic or Latino ethnicity (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations